Upaya Penghilangan Rasa Pahit Tepung Biji Kelor (Moringa oleifera) dan Aplikasinya untuk Pangan Fungsional - Muhammad Iqbal Fanani Gunawan; Endang Prangdimurti; Tjahja Muhandri (Jurnal Ilmu Pertanian Indonesia, 2020)
Moringa oleifera is a plant that has many benefits in each part. Moringa seeds have high nutrient content but they have not been used as food ingredients because it contains cyanigenic glycoside and a bitter taste. This study aims to obtain the best method in eliminating the bitter taste and cyanide of moringa seeds, analyzing its proximate nutritional levels and antioxidant capacity, and the level of acceptance when it’s applied to cookie products. This study used different types of soaking solution (water, 3.5% NaCl, 1N CH3COOH solution, and 0.5% NaHCO3) and boiling temperature (70°C, boiling water temperature (± 97°C), and pressure boiling (±115°C)). Flour with NaHCO3 immersion treatment continued by pressurized boiling for 35 minutes was chosen to be the best flour because it had the lowest cyanide content, reduced bitter taste, and the highest FRAP (Ferric Reducing Antioxidant Power) values (33.40±1.22 mg/kg; 3.40±1.24 mg/kg; and 58.70±2.67 mg AEAC/g) compared with untreated moringa seed flour (152.15±0.95 mg/kg ;10.29±2.92 mg/kg; and 17.43±1.22 mg AEAC/g). The selected flour was used as a substitute for flour (0%, 10%, 20%, and 30%) in cookies making. Sensory hedonic rating analysis on cookies used 60 untrained panelists. Substitution up to 30% overall did not have a significant difference in acceptance compared to control (0%) except for color attribute. Keywords: bitter, cyanide, Moringa oleifera, functional food, moringa seed flour